Hubungan Antara Pemakaian Tabir Surya Dengan Derajat Keparahan Melasma (Skor Masi) Pada Wanita Di Kec. Grogol-Sukoharjo - Apriliyani, Putri Yuni; , Dr. Ratih Pramuningtyas, Sp.KK (2017)
Background: Melasma is a hyperpigmentation spots on the face and can spread to the neck. Melasma is caused byUltraviolet, genetic predisposition, and hormonal changes. Ultraviolet can stimulate melanocytes to produce melanin in excessive. Sunscreen can inhibit melanogenesis induced by Ultraviolet. Purpose: To know the correlation between sunscreen and Melasma Severity Methods : This research was observational analytic with cross sectional approach. Instrument of the research were questionnare and camera. Data analysis chnique used contingency coefficient. Result: The results of the 29 respondents not use of sunscreen, 41.4% Melasma and 8.6% not melasma. Melasma can be prevented with sunscreen, because sunscreen can inhibit the Ultraviolet which can stimulate melanogenesis. The results of contingency coeffisien test known there was correlation between sunscreen and melasma severity with the value of p=0.000. Conclusion: There was correlation between sunscreen and melasma severity